2010
DOI: 10.1211/jpp.62.07.0015
|View full text |Cite
|
Sign up to set email alerts
|

Systemic chemotherapy-induced microsatellite instability in the mononuclear cell fraction of women with breast cancer can be reproducedin vitroand abrogated by amifostine

Abstract: Objectives Microsatellite instability (MSI) induction by alkylating agent-based chemotherapy (ACHT) may underlie both tumor resistance to chemotherapy and secondary leukaemias in cancer patients. We investigated if ACHT could induce MSI in tumor-derived plasma-circulating DNA (pfDNA) and in normal peripheral blood mononuclear (PBMN) cells. We also evaluated if amifostine could interfere with this process in an in-vitro model. Methods MSI was determined in pfDNA, PBMN cells and urine cell-free DNA (ufDNA) of 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There was no correlation between changes in MSI in the studied areas between the oral mucosal cells and biological matrices such as mononuclear peripheral blood DNA from urine sediment and plasma DNA of women with breast cancer (Figure 1) previously studied by Pinto et al [9] . Figure 1.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…There was no correlation between changes in MSI in the studied areas between the oral mucosal cells and biological matrices such as mononuclear peripheral blood DNA from urine sediment and plasma DNA of women with breast cancer (Figure 1) previously studied by Pinto et al [9] . Figure 1.…”
Section: Resultsmentioning
confidence: 70%
“…Previous work in our study group demonstrated induction of MSI in normal cells of the mononuclear fraction of peripheral blood DNA from urine sediment and plasma DNA of women with breast cancer undergoing chemotherapy regimen with the presence of alkylating agents [2,9] . In an in vitro model with lymphocytes exposed to alkylating agents, Marsicano and Pinto et al showed the presence of genomic instability and decrease of repair protein expression hMSH2 [9,10] .…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations